2016
DOI: 10.3390/met6020030
|View full text |Cite
|
Sign up to set email alerts
|

Ti/Al Multi-Layered Sheets: Accumulative Roll Bonding (Part A)

Abstract: Co-deformation of Al and Ti by accumulative roll bonding (ARB) with intermediate heat treatments is utilized to prepare multi-layered Ti/Al sheets. These sheets show a high specific strength due to the activation of various hardening mechanisms imposed during deformation, such as: hardening by grain refinement, work hardening and phase boundary hardening. The latter is even enhanced by the confinement of the layers during deformation. The evolution of the microstructure with a special focus on grain refinement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 44 publications
0
17
0
1
Order By: Relevance
“…Unfortunately, the homogeneity of rolling is also influenced by the deformation conditions, for example, rolling reduction, deformation rate and temperature. For example, necking in ARB Ti/Al is more pronounced when rolling is carried out at lower rolling speed …”
Section: Arb Lmcsmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, the homogeneity of rolling is also influenced by the deformation conditions, for example, rolling reduction, deformation rate and temperature. For example, necking in ARB Ti/Al is more pronounced when rolling is carried out at lower rolling speed …”
Section: Arb Lmcsmentioning
confidence: 99%
“…It has been found that in a stack of two sheets of high purity titanium between three sheets of the aluminum alloy AA5049, each having an initial thickness of 1 mm, necking during ARB can be significantly delayed by both an increased rolling speed and an IA between rolling passes . Therefore, after each rolling pass carried out without lubrication at ambient temperatures using 50% reduction, a rolling speed of 31.1 m min −1 and rolls with a diameter of 110 mm, an IA has been performed at 450 °C for 90 min.…”
Section: Selected Arb Systemsmentioning
confidence: 99%
“…This composite is composed of 160 continuous layers. For any details, please refer to part A of this study [1].…”
Section: Methodsmentioning
confidence: 99%
“…Multi-layered sheets have been obtained from a stack of three Al and two Ti sheets being alternatingly placed, i.e., Al-Ti-Al-Ti-Al, and accumulatively roll bonded as described in part A of this study [1]. This sheet could be further processed by ARB as the Al is always at the outer side of the composite which eases roll bonding.…”
Section: Differential Speed Rolling Of Ti/al-multi-layersmentioning
confidence: 99%
See 1 more Smart Citation